(untitled) (Comprehensive Journal of Science, 2025)
This study. The study included ten points inside the Mellitah Oil and Gas Complex for 7 consecutive days. Gas emissions were measured (SO2, NO2).The study aimed to study the dangers of gases resulting from petroleum complexes in the work environment and compare them with the specifications of natural air according to the World Health Organization (WHO)). The measured values of gases were within the time limits available to them and have no effect on the passage of time, but with increasing temperatures the concentration of SO2 gas during the measurement period.